Pemanfaatan dan Efektivitas Kegiatan Penangkaran Penyu di Bali bagi Konservasi Penyu - Eterna Firliansyah; Mirza Dikari Kusrini; Arzyana Sunkar (Universitas Gadjah Mada, 2017)
Sea turtle has been widely consumed in Bali since the 1970s mostly for religious activities. After many international critics, various stakeholders (governments, NGOs, environmentalists and Balinese people) developed the so-called “turtle conservation centre” as means to conserve sea turtles. The purpose of this study is to assess the effectiveness of those conservation efforts by evaluating the conservation activities of each conservation centres. We visited five sea turtle conservation centres in Bali; all were named as captive breeding centres or farm. The captive breeding centre is misleading as there is no activity related to captive breeding, mostly hatchery. Some of the eggs were not even originated from Bali, and the centres were sometimes used as the source for sea turtle for religious purposes. Based on the scoring, only one centre is active in terms of conservation. Turtle conservation program in Bali should increase their in situ program, i.e. mapping and protecting the nesting habitat and conducting regular monitoring of nesting turtle.